Ecopedagogic-Based Education to Foster Ecological Awareness in Indonesian Language Learning - Sutrisna, I Putu Gede; Bhandesa, Asthadi Mahendra; Wulansari, Nadya Treesna; Susanta, I Putu Agus Endra (Utamax : Journal of Ultimate Research and Trends in Education, 2025)
Global ecological crises such as climate change, deforestation, and pollution demand the urgent integration of sustainability values into all areas of education, including language learning. Although the Indonesian Language curriculum offers substantial potential to foster ecological awareness, its pedagogical application remains underexplored. This study aims to investigate the integration of eco-pedagogical values within Indonesian Language learning in the context of the Merdeka Curriculum at junior and senior high school levels. A qualitative descriptive approach was employed using content analysis as the central method. Primary data were obtained from national policy documents, Indonesian language textbooks, teaching modules, and curriculum frameworks. These were complemented by interview data from school principals and language teachers across Bali Province, providing insight into both institutional policy and classroom-level implementation. The analysis revealed that ecological themes are consistently embedded in various genres of language texts including descriptive, narrative, expository, and procedural forms. Topics such as biodiversity, natural disasters, environmental ethics, and conservation practices are explicitly integrated into learning materials. Key national programs including the P5 initiative, the Adiwiyata School movement, and Permendikbudristek Number 37 of 2022 play a supportive role in reinforcing these values. The findings indicate that Indonesian Language learning serves a dual purpose by enhancing linguistic competence while simultaneously cultivating students' ecological literacy and ethical responsibility. This study contributes to the advancement of language education that supports sustainable development and encourages environmentally conscious citizenship.